Mumps antibodies in the cord blood: Association with maternal recall of mumps. Possible consequences for vaccination strategies - Frade J (2020)
The present study aims to contribute to the evaluation of the serological impact of vaccination against mumps in Portugal, measuring anti-mumps IgG (MuIgG) levels in cord sera and the corresponding proportions of seropositive newborns, and their association with potential predictive variables. The data from this study came from 198 umbilical cord sera. Detailed vaccination records were available for all mothers. MuIgG were measured in the sera, using a commercial immunoassay. The geometric mean concentration (GMC) of MuIgG was 31.7 RU/ml. Seropositive/immune sera (concentration ≥16 RU/ml) were 75.3%. While 49 mothers were “unsure” about ever having had mumps, 46 said they had had the disease and 103 said they had not had it. Eighty eight women did not receive a single dose of MMR while the other received 1 or 2 doses, with different combinations of vaccine strains. This study found that recalling mumps was predictive of higher MuIgG GMC and seropositivity. Maternal age and vaccination status were not associated with GMC or seropositivity. Nevertheless, in the small subset of newborns from vaccinated mothers not recalling mumps, receiving two doses was predictive of higher GMC than just receiving one. Maternal recall of mumps is highly predictive of seropositivity while not recalling the disease results in numerous false-negatives. This is consistent with other studies and with the fact that infection with mumps virus can result in a wide range of clinical manifestations. We agree on the need for further research to support a recommendation of a three (or more)-dose MMR strategy but we also believe that evidence is fast accumulating in favour of a higher dose strategy. The issue of waning immunity due to vaccines when vaccination succeeds in controlling (and nationally eliminating) target diseases like measles and mumps must be urgently taken into account.